1977
DOI: 10.1111/j.1432-1033.1977.tb11360.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin Production by Normal and Transformed 3T3 Fibroblasts in Cell Culture

Abstract: Prostaglandin EZ and prostaglandin Fza were quantitatively determined in culture media from Balb/c 3T3 fibroblasts and two virus-transformed derivatives of these cells. Regular and (simian virus 40)-transformed 3T3 cells produced low and almost identical prostaglandin EZ concentrations. The levels were maximal (10 ng/ml) 24 h after planting and decreased during the next 96 h to 2.5 ng/ml. In contrast, polyoma-virus-transformed 3T3 cells produced prostaglandin E2 continuously for 120 h, giving a final concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

1977
1977
1987
1987

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Other primary prostaglandins represent alternative possibilities. However, E-type prostaglandins are more potent activators of adenylate cyclase in fibroblasts [27] and occur in equal or higher concentrations than other primary prostaglandins in media from cultured fibroblasts [3,7,11]. Hence, they are the most likely mediators of the rise in cyclic AMP in this system.…”
Section: Discussionmentioning
confidence: 99%
“…Other primary prostaglandins represent alternative possibilities. However, E-type prostaglandins are more potent activators of adenylate cyclase in fibroblasts [27] and occur in equal or higher concentrations than other primary prostaglandins in media from cultured fibroblasts [3,7,11]. Hence, they are the most likely mediators of the rise in cyclic AMP in this system.…”
Section: Discussionmentioning
confidence: 99%
“…Upon binding of hormones or other agonists to their respective cell surface receptor, AA is released from phospholipids through activation of phospholipases (1)(2)(3)(4)(5)(6)(7)(8)(9). In most if not all such instances, activation of phospholipases is associated with production of PGs and TXs (1,2,5,9,10). Therefore, it is generally believed that phospholipases control formation of PGs through release of AA.…”
Section: Introductionmentioning
confidence: 99%
“…The relation between phospholipase activation resulting in liberation of arachidonic acid (AA)' from complex glycerolipids and the cyclooxygenase pathway generating prostaglandins 1. Abbreviations used in this paper: AA, arachidonic acid; PDS, plasmaderived serum; PG, prostaglandin; PDGF, platelet-derived growth factor, TX, thromboxane.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, using cultured cells, it has been found that transformation by carcinogens or by viruses (Hammarstrom, 1977) is followed by increased production of PGs.…”
mentioning
confidence: 99%